Hallusinosis due to methylphenidate overdose in an eight-year-old child: a case report - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2017)
Methylphenidate, which blocks the presynaptic norepinephrine and dopamine transporters, is the most common used medication and offered as first choice in the treatment guidelines of attention deficit hyperactivity disorder (ADHD). One of its rarely seen adverse effects is, hallucinations that can be formed idiosyncratically, which can be correlated with increased dopaminergic functioning in synaptic cleft. We will present an eight year old boy diagnosed with ADHD-combined type, and oppositional defiant disorder (ODD) with no previous medical and family history who has impulsively taken extra dose of methylphenidate in the course of usual drug treatment. The acute hallucinosis presentation which has subsided the next day completely with the cessation of drug treatment will be discussed.
Keywords: Methylphenidate; Hallucinosis; Attention deficit hyperactive disorder